2009
DOI: 10.1002/anie.200901914
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Coupling of a 4‐H‐Butatrienylidene Tungsten Complex

Abstract: Tungsten tryst: A 4-H-butatrienylidene complex of tungsten was successfully isolated and structurally characterized. It undergoes a unique self-coupling, which leads to a dimer (see picture; P pink, O red) with a cross-conjugated pi system and with electrochemically and magnetically active metal centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
20
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 34 publications
2
20
0
Order By: Relevance
“…Substituted DEBDs are scattered through the literature,w ith single examples from the groups of Larock, [5] Gleiter, [6] Grigg, [7] and Suzuki, [8] three compounds from Faust, [9] and three from Hopf, [10] including the parent hydrocarbon 1.R u, Fe,a nd W complexes containing DEBDs,w hich display interesting electronic properties,h ave been studied by Bruce [11] and others. [12] Thec ontribution from the Hopf group uncovered almost everything that is known about the reactivity of DEBDs and identified interesting applications.H opf and co-workers reported the Diels-Alder reaction of their compounds with dienophiles to prepare cyclic Z-endiynes, [10] which found application in both Bergman cycloaromatizations [13] and in the synthesis of substituted phthalocyanines with potential in photodynamic therapy. [9] Hopf also reported the formation of 1,4-cyclooctadienes through the thermal [4+ +4]-cycloaddition dimerization of DEBDs.T his remarkable transformation represents af ormally disallowed process according to the Woodward-Hoffmann rules.…”
Section: Introductionmentioning
confidence: 99%
“…Substituted DEBDs are scattered through the literature,w ith single examples from the groups of Larock, [5] Gleiter, [6] Grigg, [7] and Suzuki, [8] three compounds from Faust, [9] and three from Hopf, [10] including the parent hydrocarbon 1.R u, Fe,a nd W complexes containing DEBDs,w hich display interesting electronic properties,h ave been studied by Bruce [11] and others. [12] Thec ontribution from the Hopf group uncovered almost everything that is known about the reactivity of DEBDs and identified interesting applications.H opf and co-workers reported the Diels-Alder reaction of their compounds with dienophiles to prepare cyclic Z-endiynes, [10] which found application in both Bergman cycloaromatizations [13] and in the synthesis of substituted phthalocyanines with potential in photodynamic therapy. [9] Hopf also reported the formation of 1,4-cyclooctadienes through the thermal [4+ +4]-cycloaddition dimerization of DEBDs.T his remarkable transformation represents af ormally disallowed process according to the Woodward-Hoffmann rules.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that this reaction proceeds via a 1,2-bis(ethynyl)cyclobutenyl diradical intermediate which undergoes retro-electrocyclic ring opening. 27 A recent experimental and theoretical investigation on iron and ruthenium σ-polyynyl complexes has concluded that the iron(III) radicals bearing ligands with four and six sp carbon atoms are stable in solution for a few minutes at 20 °C and for an unlimited time below −20 °C. It was also suggested that the 17e iron radicals may react via a smooth chemical process, since the ESR signal disappeared cleanly, no traces of other radicals being detected.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Related to this chemistry is the earlier report of the dimerization of the butatrienylidene (dppe) 2 (CO)W{CCCCH(C 6 H 4 Bu t )} to give {(dppe) 2 (CO)W}{CC[CH(C 6 H 4 Bu t )]C[CH(C 6 H 4 Bu t )]CC}{W(CO)(dppe) 2 } by C γ –C γ coupling. It has been suggested that this reaction proceeds via a 1,2-bis(ethynyl)cyclobutenyl diradical intermediate which undergoes retro-electrocyclic ring opening …”
Section: Introductionmentioning
confidence: 99%
“…Typical spectroscopic features of 6 are the singlet at d 5.73 for the QCH proton in the 1 H NMR spectrum and the four distinct signals for the carbon atoms of the RhC 4 chain in the 13 C NMR spectrum. These signals exhibit quite different 13 C-103 Rh and 13 C-31 P coupling constants. It is worth mentioning that the chemical shifts of the resonances for the cumulene carbon atoms in a-, band g-position (d 237.3, 161.1 and 173.1) are rather similar to those of the IrC 4 counterpart trans-[IrCl(QCQCQ CQCPh 2 )(PiPr 3 ) 2 ] (d 225.7, 164.1 and 174.6).…”
mentioning
confidence: 98%
“…It has been characterized by the mass spectrum and by reference to the IR and NMR spectroscopic data. 13 Reaction of either 7 or 8 with triflic acid in the presence of an equimolar amount of water gives the rhodium(I) vinylidene complex 9 (Scheme 2) as an orange solid, which for short periods of time can be handled in air. The IR spectrum of 9 shows a strong band at 1640 cm À1 , assigned to the CQO stretching mode of the ketone unit.…”
mentioning
confidence: 99%